2020
DOI: 10.48550/arxiv.2005.03082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploratory Analysis of Covid-19 Tweets using Topic Modeling, UMAP, and DiGraphs

Abstract: This paper illustrates five different techniques to assess the distinctiveness of topics, key terms and features, speed of information dissemination, and network behaviors for Covid19 tweets. First, we use pattern matching and second, topic modeling through Latent Dirichlet Allocation (LDA) to generate twenty different topics that discuss case spread, healthcare workers, and personal protective equipment (PPE). One topic specific to U.S. cases would start to uptick immediately after live White House Coronaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 39 publications
(58 reference statements)
1
37
0
Order By: Relevance
“…al. [32] did a thorough analysis of COVID-19 tweets using topic modeling and pattern matching to identify high-level trends, events with sudden spikes, distinctive topics, speed of tweeting and retweeting, and network behaviors. On a similar topic, Kwan and Lim [33], [34] used sentiment analysis, topic modeling and temporal analysis techniques on tweets to study trends and discussions about COVID-19 in various countries.…”
Section: Trend Analysis Using Publicationsmentioning
confidence: 99%
“…al. [32] did a thorough analysis of COVID-19 tweets using topic modeling and pattern matching to identify high-level trends, events with sudden spikes, distinctive topics, speed of tweeting and retweeting, and network behaviors. On a similar topic, Kwan and Lim [33], [34] used sentiment analysis, topic modeling and temporal analysis techniques on tweets to study trends and discussions about COVID-19 in various countries.…”
Section: Trend Analysis Using Publicationsmentioning
confidence: 99%
“…Cinelli et al [1] extract topics with word embedding on a global scale, making the conclusion that social media may help to design more efficient epidemic models for social behaviour and to implement more efficient communication strategies. The LDA model is used by Medford et al [5] and Ordun et al [6] to analyse the topics in early period of the pandemic. Sharma, et al [7] use character embedding [28] and Term Frequency Inverse Document Frequency (TF-IDF) word distribution with manual inspection for topic modelling.…”
Section: Related Workmentioning
confidence: 99%
“…There is a growing body of research that links OSNs activities to COVID-19. Some existing results have already shown that OSNs conversations can be a leading indicator of COVID-19 cases [2,3], discussions on OSNs can be categorised into multiple specific topics [4,5,6,7] and OSNs may help to design more efficient pandemic models for social behaviour and to implement more responsive government communication strategies [1,8,9]. However, there are three main problems with the existing research.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, in [2], Kleinberg et al presented a ground truth dataset of emotional responses to COVID-19, and presented a framework to detect the main concerns of people in different countries on COVID-19 subject. In [3], Ordun and colleagues analyzed five different techniques to assess the distinctiveness of topics, key terms and features, speed of information dissemination, and network behaviors for Covid-19 related tweets. In [4], Singh et al looked at the information and misinformation shared on Twitter.…”
Section: Introductionmentioning
confidence: 99%